Johannes Cocceius: Federal Theologian - McCoy, Charles S. (Scottish journal of theology, 1963)
Ours is an age not only of discovery but also of rediscovery. By some process of reincarnation in the history of ideas, eras of the past remembered with reproach have successively come to be regarded as wellsprings offruitful thought. Medieval philosophy, once treated with deprecation as illustrating the enslavement of reason to theology, has acquired respect and been reborn in a vigorous neo-Thomism. Reformation thought, considered hopelessly obscurantist by disciples of Enlightenment, has found rebirth through powerful theological spokesmen and a hearing far beyond the confines of the organised churches. Biblical theology, reinvigorated by nineteenth-century investigation of Scripture and given impetus by Reformation doctrinal motifs, has enjoyed a renaissance in recent decades.